1994
DOI: 10.1055/s-2007-1021061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training Modality on Glucose Tolerance in Men with Abnormal Glucose Regulation

Abstract: To determine the effects of exercise training modality on glucose tolerance in men with untreated abnormal glucose regulation, 26 untrained men (age 54 +/- 9 years; mean +/- SD) with either non-insulin-dependent diabetes mellitus (N = 8), impaired glucose tolerance (IGT) (N = 12) or hyperinsulinemia with normal glucose tolerance (N = 6) were studied before and after 20 wk of either strength training (ST) (N = 8), aerobic (treadmill walk/jog) training (AT) (N = 8), or no exercise (control group; N = 10). Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
1
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 24 publications
11
53
1
8
Order By: Relevance
“…Of the studies otherwise meeting the inclusion criteria, two trials (three articles) were not included since the fitness test was not a maximal aerobic test [35,36,37], three trials (four articles) were excluded because they included a large resistance training component combined with non-continuous aerobic exercise [38,39,40,41] and two articles were excluded since we were unable to differentiate between subjects with and without diabetes [42,43]. Four of the potential articles did not have baseline and post-training VO 2max data available [44,45,46,47] while one trial (two articles) measured post training VO 2max 6 months after the initiation of the 10-week exercise intervention [48,49] and was therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies otherwise meeting the inclusion criteria, two trials (three articles) were not included since the fitness test was not a maximal aerobic test [35,36,37], three trials (four articles) were excluded because they included a large resistance training component combined with non-continuous aerobic exercise [38,39,40,41] and two articles were excluded since we were unable to differentiate between subjects with and without diabetes [42,43]. Four of the potential articles did not have baseline and post-training VO 2max data available [44,45,46,47] while one trial (two articles) measured post training VO 2max 6 months after the initiation of the 10-week exercise intervention [48,49] and was therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the changes in central adiposity in the progressive resistance training group were associated with increases in strength, while in the control group alone strength change was not a significant predictive factor for the change in waist circumference. Adult studies have found that resistance training improves muscle mass, strength and insulin sensitivity 56,57 and decreases visceral fat 5-7 although it is not clear whether these linked benefits are due to changes in energy expenditure (resting metabolic rate and physical activityrelated expenditure), muscle metabolism, insulin regulation, counter-regulatory hormones or adipokines induced by exercise. [58][59][60] In our short-term study, we did not hypothesize that fat-free mass would improve significantly or underlie the changes in fat mass or associated metabolic benefits, but in longer term progressive resistance training interventions in children it would be important to measure all body composition adaptations (muscle, bone, fat) to ascertain the relationships between adaptations in these body tissues during maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous longer-term resistance training studies alone (17,18,20) or in conjunction with energy restriction (19) have demonstrated significant improvements in insulin action and glucose utilization. One major methodological difference is that metabolic parameters were reassessed 24 h after the last exercise session in those studies, whereas glucose disposal was measured 72 h after resistance training in the current study.…”
Section: Hyperinsulinemic-euglycemic Clampmentioning
confidence: 99%
“…Resistance training (RT) increases insulin sensitivity in older men and women (17)(18)(19)(20). Combining moderate energy restriction with resistance training preserves lean tissue mass and substantially reduces body fat mass (FM) (21,22).…”
mentioning
confidence: 99%